Risk factors of insulin refusal among type 2 diabetes mellitus patients with poor glycaemic control at Tanglin Health Clinic, Kuala Lumpur - Simon, Puvanese Rebecca Pillai; Md Said, Salmiah; Azman, Ahmad Zaid Fattah; Shah, Shamsul Azhar (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: The number of patients with poor glycaemic control who refuse insulin therapy is alarming. Factors that contribute to insulin refusal are important to study to identify high risk groups so that appropriate measures can be taken to prevent progression of uncontrolled diabetes. The objective of this study is to determine the risk factors of insulin refusal among type 2 diabetes mellitus patients with poor glycaemic control at Tanglin Health Clinic, Kuala Lumpur, Malaysia. Methods: A case control study was conducted among 216 cases and 230 controls using stratified sampling method. Cases were defined as patients with HbA1C more than 7.5% but not on insulin therapy despite being offered by the doctor whereas controls consist of patients with HbA1C of more than 7.5% but already on insulin therapy. Data was collected from April until May 2018, using a self-administered questionnaire. Analysis was done via IBM SPSS version 23.0. Results: Response rate for cases was 93.9% and response rate for controls was 100%. Risk factors of insulin refusal among poor glycaemic control includes age above 60 years old, tertiary level education, duration of diabetes less than 10 years, poor level of knowledge on insulin, fear on injection pain and fear to bruising due to injections. Conclusion: Hence, efforts must be taken to tackle the modifiable factors such as knowledge on insulin and diabetes, and fear on injections and bruises.